Is there a difference? Contrasting experiences of face to face and online learning - Asensio, Mireia; Hodgson, Vivien; Trehan, Kiran (Proceedings of the International Conference on Networked Learning, 2000)
In this paper we examine the differences and similarities of the participants' experiences in working in face to face and online learning environments. The descriptions of experiences in collaborative assessment are particularly revealing, in chat the emotional content associated with the process is shared by the participant’ of both environments. We point out a difference in the way the online participants communicated with each other and believed that they had become more interpersonally aware and more interpersonally effective. This leads us to consider to what extent the online environment can support the extension of interpersonal communication skills, as equally or in greater ways than face to face. The work on Derrida on the speech/writing dichotomy, has provided a framework of analysis to understand writing as an equal form of communication for the expressions of thoughts and feelings.